The Implementation of Animal Biotechnology to Control the Supply and Quality of Duck Eggs in Malaysia - Raja Muhammad Naufal, Hj Raja Taufik Azad; Syaza Nureirina, Mohd Razif; Muhammad Qayyum Haikal, Abdul Hadi; Nor Atirah, Suderman; Nur Aida Husna, Ab Halim; Hung Hui, Chung (UNIMAS Publisher, 2025)
Malaysia’s poultry industries are leading the way in satisfying the population’s demand. According to statistics, Malaysia is the third largest producer of duck after China and France, and production has significantly expanded during the past ten years. Malaysians consume an average of 320 eggs per person annually, which ranks as top consumers worldwide, far higher than United States (average of 250 eggs annually) and India (average of 48 eggs annually). Furthermore, regardless of their culture or religion, people in Asian nations consume eggs and egg-related items (Quan & Benjakul, 2019). Similar to hens, ducks can be raised for egg productions as well. However, as compared to chicken eggs, the prevalence of duck eggs is higher. Besides, the production of duck eggs is higher with 300-350 eggs production with greater weight of 32-34 ounces per dozen annually as compared to an average of annual production of 250 chicken eggs with lesser weight (24-26 ounces). Despite of greater feed (20-30%) are needed for ducks than chickens raise per dozen eggs, ducks possess the ability to forage for their nutritional needs (National Institute of Food and Agriculture, 2023).